European Small Business Finance Outlook: December 2018 - Helmut Kraemer-Eis; Antonia Botsari; Salome Gvetadze; Frank Lang; Wouter Torfs (European Investment Fund (EIF), 2018)
This analysis provides an overview of the main markets relevant to the EIF. It starts by discussing the general market environment, then looks at the main aspects of equity finance and the guarantee and SME securitisation markets and, finally, it highlights important aspects of microfinance in Europe. A chapter on Fintech also complements the analysis. The EIF Working Papers are designed to make available to a wider readership selected topics and studies in relation to EIF's business. The Working Papers are edited by EIF's Research & Market Analysis and are typically authored or co-authored by EIF staff or are written in cooperation with EIF.
Keywords: 330